Universal orthologs infer deep phylogenies and improve genome quality assessments - Md Nafis Ul Alam; Cristian Román-Palacios; Dario Copetti; Rod A. Wing (BMC Biology)
Abstract Background Universal single-copy orthologs are the most conserved components of genomes. Although they are routinely used for studying evolutionary histories and assessing new assemblies, current methods do not incorporate information from available genomic data. Results Here, we first determine the influence of evolutionary history on universal gene content and find that across 11,098 genomes of plants, fungi, and animals comprising 2606 taxonomic groups, 215 groups significantly vary from their respective lineages in terms of BUSCO (Benchmarking Universal Single Copy Orthologs) completeness. Additionally, 169 groups display an elevated complement of duplicated orthologs, likely from ancestral whole genome duplication events. Secondly, we investigate the extent of taxonomic congruence in broad BUSCO-derived phylogenies. For 275 suitable families out of 543 tested, sites evolving at higher rates produce at most 23.84% more taxonomically concordant, and at least 46.15% less terminally variable phylogenies compared to lower-rate sites. We find that BUSCO concatenated and coalescent trees have comparable accuracy and conclude that higher rate sites from concatenated alignments produce the most congruent and least variable phylogenies. Finally, we show that undetected, yet pervasive BUSCO gene loss events lead to misrepresentations of assembly quality. To overcome this, we filter a Curated set of BUSCOs (CUSCOs) that provide up to 6.99% fewer false positives compared to the standard search and introduce novel methods for comparing assemblies using gene synteny. Conclusions Overall, we highlight the importance of considering evolutionary histories during assembly evaluations and release the phyca software toolkit that reconstructs consistent phylogenies and offers more precise assembly assessments.